No Matter, Never Mind : Proceedings of Toward a Science of Consciousness : Fundamental Approaches (Tokyo '99) - Yasue, Kunio; Jibu, Mari; Della Senta, Tarcisio (Advances in consciousness research, 2002)
Annotation This international selection of 34 papers from the Tokyo '99 conference held at the United Nations University gives a valuable state of the art overview of consciousness research. Not only the recognized European and American approaches but also the distinguishing approaches from many Japanese researchers are presented. It will provide a world-wide audience with a comprehensive outlook for the remarkable potential contribution in the future scene of consciousness research. The Tokyo '99 declaration to promote scientists ethical warning against the thoughtless aiming of consciousness research at warfare is also included.(Series B).